Peningkatan Motivasi dan Jiwa Entrepreneurship Menuju Kehidupan Yang Lebih Berkualitas Aspek Social Mapping Panti Sosial Bina Taruna Jaya 2 - Maria Ariesta Utha; Dita Oki Berliyanti; Idrianita Anis; Debbi Andalia; Supriadi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2022)
Panti Sosial Bina Remaja Taruna Jaya 2 has been owned by the DKI Jakarta Provincial Government since 1999 and is a Technical Implementation Unit in fostering youth with social problems. The mission of Panti Sosial Bina Remaja Taruna Jaya 2 is to form teenagers with social problems into teenagers with good personalities through physical, psychological, mental spiritual, social and work skills development in order to realize independence and social functioning by establishing cross-sectoral coordination. For this reason, the Faculty of Economics and Business, Trisakti University, together with the DKI Jakarta Social Service and the DKI Jakarta CSR Forum, have created a partnership in overcoming the problems of youth with social problems through the development of soft skills and hard skills. and participate in providing solutions and actively participate in activities to increase motivation and shape the entrepreneurial character of social development residents.